Induced pathomorphism and manifestations of residual focal lesions in parenchymatous organs of patients after noninvasive procedures - Z. A. Lemeshko; A. V. Borsukov; A. V. Mamoshin; T. G. Morozova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To reveal principles of development residual focal lesions various type and location in parenchymatous organs of patients after different noninvasive medical manipulations.Material and methods. Overall 365 patients with focal lesions: metastases and cysts of the liver, residual foci in gallbladder area after endoscopic obliteration of organ cavity, malignant tumors and pseudo-cysts of the pancreas, chronic pancreatitis, abscesses of abdominal cavity of various localization, cysts and tumors of the spleen, cysts and tumors of kidneys, focal goiter, fibrous adenoma of breast gland were studied. Total of 1281 noninvasive medical manipulation at ultrasound guidance and X-ray navigation — installation of drainages/catheters and local treatment by antibiotics, intraportal injection of pharmaceuticals, sclerotherapy of 96% ethyl alcohol of liver and kidney cysts, metastases to the liver, interstitial laser photocoagulation of focal goiter, radio-frequency ablation of metastases in the liver, electrochemical destruction of liver metastases and fibrous adenomas of breast gland etc. was carried out. Ultrasound investigation was the basic diagnostic and control method; while helical x-ray computer tomography, X-ray fistulography, endoscopic retrograde cholangiopancreatography, scintigraphy, elastography, diagnostic punctures (aspiration biopsy, core needle biopsy, transcutaneous transhepatic cholangiography), laparoscopy, laparotomy, morphological investigation were used as methods of verification and control. Patients were followed up for 5 to 15 and more years.Conclusion. It was revealed, that residual focal lesions of various type and location in parenchymatous organs after noninvasive procedures have similar consecutive stages of development, caused by common (clinical, pathomorphological) features.